Exploring the Landscape: A Systematic Review of the Tamil Reading Development Framework - Safeek, N.M.M.; Ponniah, K. (The International Society for Technology, Education and Science (ISTES), 2024)
Chapter Highlights ➢ Reading exerts a profound and lasting influence on children's lives, commencing in early childhood and extending throughout their entire lifespan. ➢ While the science of reading has predominantly drawn upon research conducted in English and other languages, the application of certain reading framework components to Tamil language-based instruction poses challenges. ➢ Tamil possesses unique linguistic features that diverge from English and Western languages. In response, this study aims to introduce a Smart Reading Module-based (SRM) teaching intervention designed for Tamil children, whether they encounter reading difficulties or not. ➢ To formulate this intervention, the researcher conducted an extensive systematic review, encompassing 90 empirical studies conducted between 2016 and 2023, all endorsing skill-based interventions targeting reading development. ➢ The findings robustly support the efficacy of the SRM-based teaching intervention model in cultivating reading fluency among children, especially those grappling with reading challenges. ➢ This comprehensive intervention encompasses critical elements, including phonological awareness, word-sound mapping, syllabic and morphological comprehension, syntactic understanding, semantic proficiency, and adeptness in reading comprehension. ➢ By accommodating the distinct linguistic characteristics of the Tamil language, this SRM-based approach strives to empower Tamil children on their journey towards becoming proficient and confident readers.
Keywords: Systematic Review; Tamil Language; Reading